Investigation on effect of magnetite nanofluid on performance and emission patterns of methyl esters of bio diesel - Yuvarajan D; Venkata Ramanan M (Journal of environmental engineering and landscape management, 2016)
The objective of this work is to reduce viscosity and other related problems associated with biodiesel by adding non polluting additives. Magnetite is chosen as an additive in this work. Significant reason for using magnetite as an additive is that the magnetic nano particles (magnetite) can be collected from exhaust using magnetic billets in the tail pipe.  Performance and emission test is carried out in single cylinder compression ignition engine using base and modified fuel and is compared to diesel.  Modified fuel consists of 98.5% base fuel (Rice bran oil methyl ester), 1.3% additives (magnetite) and 0.2% surfactant (tri methyl ammonium hydroxide) by volume. The experimental work confirmed that by adding magnetite to methyl esters of rice bran oil enhances the brake thermal efficiency by 4.27% with 5.17% reduction in SFC. In addition, 10.8%, 9.1% and 8.49% reduction in HC, CO and nox emissions is observed respectively.